Biosensing of Interaction between Liposome of Model Cell Membrane and Amyloid-Beta Protein by Dielectric Dispersion Analysis. (2015) - Yoshikawa, Tomoki; Zhang, Ziyang; Yamashita, Kaoru; Noda, Minoru
Abstract: We have investigated time course of interaction between liposome and amyloid-beta protein (Aβ) by Dielectric Dispersion Analysis (DDA), especially for frequency range over 1 GHz. Observed dielectric relaxations showed that their relaxation width changes with time and the change depends on the concentration of Aβ. It is considered that the dynamics of relaxation width is related to the aggregation and fibrillization of Aβ protein. In particular, a low concentration of Aβ (1 μM) has been successfully discriminated this time. We expect that this technique can be applied to biomedical sensing for Aβ detection.